Efektivitas layanan informasi menggunakan teknik problem-based learning untuk meningkatkan self regulated learning siswa - Sari, Ariska Srinika; Syukur, Yarmis (IICET (Indonesian Institute for Counseling, Education and Therapy), 2023)
This research is motivated by the problems of students' self-regulated learning . This can be seen in the students when studying, there is no preparation for learning by students, students do not pay attention to the teacher during learning activities, lack of student responsibility for the assignments given by the teacher. Efforts made to improve student self-regulated learning are information services using a problem-based learning approach. The aims of this study were (1) to analyze the differences in the self-regulated learning of students in the experimental group before and after being given information services using a problem-based learning approach, (2) to analyze the differences in self-regulated learning of students in the control group before and after being given information services without using a problem-based approach learning, (3) testing the effectiveness of information services using a problem-based learning approach to improve student self-regulated learning . This study used an experimental design with a pretest and posttest control group design. The subjects in this study were 70 students at MTsN 1 City of SungaiFull, with a low self-regulated learning category . The instrument used in this study is a self-regulated learning instrument with a Likert scale. The technique used by purposive sampling. Data were analyzed using the Wilcoxon Signed Ranks Test and the Kolmogrof Smirnov 2 Independent Sample test with the help of SPSS version 20.00. The results of this study indicate that information services using a problem- based learning approach are effective in increasing student self-regulated learning . The results of this study can be used as a reference in assisting counseling guidance service programs, especially using a problem-based learning approach to overcome students' low self-regulated learning.